Regionalization : an analytical study on the mode of entry of Singapore-based firms. - Goh, Keng Wee. (2008)
This study aims to determine the rationale behind the adoption of various entry modes by Singapore-based firms when regionalizing. The study adopts a structured and systematic approach proposed by Franklin R. Root (1994), while incorporating from other sources of literature.